Managers and management in Vietnam : 25 years of economic renovation (doi moi) - Edwards, Vincent, 1947-; Phan, Anh. (New York : Routledge, 2013)
"This book presents a comprehensive overview of managers and management in Vietnam, based on extensive original research, including interviews with a large number of managers in Vietnam. It shows how management in Vietnam is best understood from the perspective of Vietnamese managers themselves, rather than in terms of Western or Asian models of management."--Publisher's description.
Philosophical foundations -- The evolution and structure of the Vietnamese economy -- Company contexts -- The evolution of Vietnamese management -- Sense and sensibility -- Development and self-development : organizational insights (1) -- Development and self-development : organizational insights (2) -- Development and self-development : east and west -- Characterizing Vietnamese managers and management -- Whither Vietnamese management?.
Includes bibliographical references (pages [122]-128) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Management -- Vietnam; Executives -- Vietnam; Vietnam -- Economic conditions -- 1975-; Electronic books